Analysis of Road Infrastructure Development Implementation in Enhancing Public Satisfaction in Lebak Regency - Dian Purnamasari Abidin; Hasyim Adnan; Mandarina Mandarina (ijd-demos, 2024)
Abstract Road infrastructure development serves as a cornerstone for driving economic activity and regional integration at the local level. This study aims to analyze the implementation of road infrastructure development and its impact on public satisfaction in Lebak Regency. A descriptive-qualitative research method was employed, utilizing data collection techniques such as in-depth interviews with officials from the Public Works and Spatial Planning Agency (PUPR), field observations of physical road conditions, and document analysis. The findings indicate that the technological shift to concrete paving (rigid pavement) on major corridors has significantly enhanced accessibility, mobility, and economic productivity for residents. However, a stark spatial disparity exists between the northern urban areas and the remote southern regions of Lebak, resulting in a sharp polarization of public satisfaction levels. Key obstacles to policy implementation include limited fiscal space within the regional budget (APBD), landslide-prone topography, and the prevalence of overloaded vehicles that accelerate road deterioration. The study recommends diversifying funding sources by optimizing Corporate Social Responsibility (CSR) funds and the Special Allocation Fund (DAK), strictly enforcing vehicle tonnage regulations, and digitizing complaint systems to ensure transparency and provide the public with reliable information regarding road repair schedules. Keywords: Road Infrastructure, Development Implementation, Public Satisfaction, Lebak Regency.